SYNTACTICAL ASPECT OF ELLIPTICAL DIRECT DIRECTIVE ILLOCUTIONARY ACT - Nira Sifaul Hayat Ridwanullah; Tatan Tawami (MAHADAYA: Jurnal Bahasa, Sastra, dan Budaya, 2021)
One of the ways to utter the directive illocutionary act is by directly saying the intention explicitly using specific imperative structure. In other words, the directive illocutionary act has the linked structure and the function to the imperative structure that is to cause the hearer does the action speaker wants. However, In order to emphasize the direct directive illocutionary act, the speaker utters only the prior clause to convey the message. This notion is specified as the elliptical imperative. However, the structure uttered by the speaker does not always in full sentence, it could only consist of prior clause; verb phrase, object, adverb of time, etc. From that notion, this paper aims to discover the deep structure of the elliptical direct directive and the choice of prior clause as Searle (1976: 17) elaborated the structure of the directive illocutionary act as: I Verb You + You Fut.Verb (NP) (Adv). In order to analyze the data, the Qualitative descriptive is used in this paper. In conclusion, the direct directive illocutionary can be uttered in a short way by only uttering the prior clause of the locutionary such as: the verb, adverb of time, adverb of manner, and subject. Furthermore, the speakers should; utter previous locutionary as the reference for the short directive, utter the short directive when the action is performed by the hearer.